The Implementation of the Value of Mutual Cooperation in the Tradition of Grave Almsgiving as an Expression of Peace in the Community of Gempol Village, Cirebon Regency - Nurizzati, Yeti; Praditha Ayu Pertiwi, Nindy (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2026)
In this era of globalisation, the noble values inherited from the ancestors of the Indonesian people are beginning to fade or even disappear; one example is the value of mutual cooperation. In the past, communities always carried out activities for the common good through mutual cooperation, but this has now changed due to the tide of globalisation. However, not all regions have lost the value of mutual cooperation; there are still some areas that continue to uphold it. Gempol Village is one of several villages in Gempol Sub-district, Cirebon Regency, whose community still implements the value of gotong royong in the practice of the grave almsgiving tradition. The aim of this study is to identify the values of gotong royong embodied in the practice of the grave almsgiving tradition. The research method employed in this study is qualitative, utilising an ethnographic approach. The data collection techniques used in this study were observation, interviews, and documentation. The findings revealed that the practice of the grave almsgiving tradition embodies values of mutual cooperation, including solidarity, unity, voluntarism, kinship, self-sacrifice, prioritising the common good over personal interests, and mutual assistance in order to bring about peace in the community of Gempol Village.